Cytoreductive radical prostatectomy after chemohormonal therapy in patients with primary metastatic prostate cancer - Christa Babst; Thomas Amiel; Tobias Maurer; Sophie Knipper; Lukas Lunger; Robert Tauber; Margitta Retz; Kathleen Herkommer; Matthias Eiber; Gunhild von Amsberg; Markus Graefen; Juergen Gschwend; et al. (Asian Journal of Urology)
Objective: Cytoreductive radical prostatectomy (cRP) has been proposed as local treatment option in metastatic hormone-sensitive prostate cancer (mHSPC) to prevent local complications and potentially improve oncological outcomes. In this study, we examined the feasibility of a multimodal concept with primary chemohormonal therapy followed by cRP and analyzed prostate size reduction under systemic treatment, postoperative complication rates, as well as early postoperative continence. Methods: In this retrospective study, 38 patients with mHSPC underwent cRP after primary chemohormonal therapy (3-monthly luteinising hormone-releasing hormone-analogue + six cycles 3-weekly docetaxel 75 mg/m2) at two centers between September 2015 and December 2018. Results: Overall, 10 (26%) patients had high volume and 28 (74%) patients had low volume disease at diagnosis, according to CHAARTED definition. Median prostate-specific antigen (PSA) decreased from 65 ng/mL (interquartile range [IQR] 35.0–124.5 ng/mL) pre-chemotherapy to 1 ng/mL (IQR 0.3–1.7 ng/mL) post-chemotherapy. Prostate gland volume was significantly reduced by a median of 50% (IQR 29%–56%) under chemohormonal therapy (p = 0.003). Postoperative histopathology showed seminal vesicle invasion in 33 (87%) patients and negative surgical margins in 17 (45%) patients. Severe complications (Grade 3 according to Clavien-Dindo) were observed in 4 (11%) patients within 30 days. Continence was reached in 87% of patients after 1 month and in 92% of patients after 6 months. Median time to castration-resistance from begin of chemohormonal therapy was 41.1 months and from cRP was 35.9 months. Postoperative PSA-nadir ≤1 ng/mL versus >1 ng/mL was a significant predictor of time to castration-resistance after cRP (median not reached versus 5.3 months; p<0.0001). Conclusion: We observed a reduction of prostate volume under chemohormonal therapy going along with a low postoperative complication and high early continence rate. However, the oncologic benefit from cRP is still under evaluation.